The Role of Student Engagement in Mediating Learning Motivation and Learning Discipline on Economic Learning Outcomes - Dian Amaliana; Kardoyo (Universitas Negeri Semarang, 2024)
The aims of this study is to analyse the effect of learning motivation and learning discipline on learning outcomes of economic subjects through student engagement at SMA Negeri 16 Semarang. The population in this study are class students XI IPS SMA Negeri 16 Semarang, with the total amount 107 students. The sampling technique is proportional random sampling and obtained a sample of 85 students. The method of collecting data used the questionnaires and documentation methods. The data analyzed using descriptive analysis, multiple linear regression test, and sobel test. The results show that there was no positive and significant effect of learning motivation on learning outcomes of 1.29%, there was a positive and significant effect of learning discipline on learning outcomes of 7.18%, there was a positive and significant effect of student engagement on learning outcomes of 16.52%, there was a positive and significant effect of learning motivation on student engagement of 5.66%, there was a positive and significant effect of learning discipline on student engagement of 29.48%, there was a positive and significant effect of learning motivation on learning outcomes through student engagement of 14.3%, there was a positive and significant effect of learning discipline on learning outcomes through student engagement of 38%. Based on these results, it can be concluded that the student engagement is proven to be a mediating variable strengthens the influence of learning motivation and learning discipline on student learning outcomes.